Pulsed laser ablation of ultra-hard structures: generation of tolerant freeform surfaces for advanced machining applications - Pacella, Manuela (2014)
This thesis covers the laser generation of novel micro-cutting arrays in ultra-hard super-abrasive composites (e.g. polycrystalline diamond, PCD and polycrystalline cubic boron nitride, PCBN). Pulsed laser ablation (PLA) has been used to manufacture repeatable patterns of micro cutting/abrasive edges onto micro structurally different PCD/PCBN composites. The analysis on the influence of microstructural factors of the composite materials in the use of laser ablation technology has been carried out via a novel technique (Focused Ion Beam/High Resolution Transmission Electron Microscopy/Electron Energy Loss Spectroscopy) to identify the allotropic changes occurring in the composite as a consequence of PLA allowing the laser ablated PCD/PCBN surfaces to be characterized and the nanometric changes evaluated. The wear/failure characteristics/progression of the ultra-hard laser generated micro cutting/abrasive arrays has been studied in wear tests of Silicon Dioxide workpiece shafts and the influence of the microstructural factors in the wear properties of the super-abrasive micro cutting edges has been found. Opposing to these highly-engineered micro cutting/abrasive arrays, conventional electroplated abrasive pads containing diamond and CBN abrasives respectively have been chosen as benchmarks and tested under the same conditions. Contact profiling, Optical Microscopy and Environmental Scanning Electron Microscopy have been employed for the characterization of the abrasive arrays/electroplated tools before/during/after the wear/cutting tests. In the PCD abrasive micro-arrays, the type of grain and binder percentage proved to affect the wear performances due to the different extents of compressive stresses occurring at the grain boundaries. Mixed grained PCD arrays performed 25% better than fine grained arrays. All of the PCD laser manufactured arrays showed an increase up to 60% in the tool life when compared to the benchmarked pads. As for the PCBN abrasive micro-arrays, the laser manufactured arrays proved to perform 50% better than the electroplated ones in terms of wear resistance.